Uji Stabilitas Sediaan Mikroemulsi Menggunakan Hidrolisat Pati (DE 35–40) Sebagai Stabilizer - Jufri, Mahdi; Anwar, Effionora; Utami, Putri Margaining (Majalah Ilmu Kefarmasian, 2006)
Various solubilization techniques have been developed to enhance the bioavailability of hydrophobic drugs. One of the solubilization techniques is preparation of microemulsion. Microemulsion is a potential carrier in drug delivery system because it has many advantageous characteristics. In this research, hydrophobic drug was made in a dosage form of oil in water (O/W) microemulsion using ketoprofen as a model and investigated the influence of adding starch hydrolisates with dextrose equivalent (DE) 35-40 in variety concentrations (0,0%; 1,5%; 2,0%; 2,5%) to the stability of this microemulsion system. This microemulsion consisted of isopropyl miritate as oil phase, tween 80 and lechitin as surfactants, ethanol as cosurfactant, propylene glycol as cosolvent, starch hydrolisates DE 35Â–40 as stabilizer, and water as external phase. The evaluation was stability test both phisically and chemically. The result showed that the stability of microemulsion system increased significantly by adding starch hydrolisates DE 35-40 at 2,5%.